Debt costs during life cycles of listed companies in the Tehran stock exchange / Zahra Hajiha and Mohammad S. Bazaz - Hajiha, Zahra; S. Bazaz, Mohammad (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2020)
The main goal of this research was to study the relationship between life cycles and debt costs of listed companies in the Tehran Stock Exchange. Intended to be an applied research, this study used a correlational method. The statistical sample consisted of 107 listed companies for a ten-year period from 2005 to 2014, which were examined by regression models. Life cycle was the dependent variable and debt cost the independent variable. The Dickinson's Model (2011) was used to measure life cycle. This research found that debt cost was not lower during the slow stage of the life cycle than during the maturity and emergence stages, but debt cost was lower in the growth and decline stages.